MANAGEMENT OF ECONOMIC INTERACTIONS IN THE LABOR MARKET IN THE REPUBLIC OF UZBEKISTAN BASED ON THE GRAVITY MODEL (Marketing Journal, 2026)
This article is devoted to the quantitative assessment of interregional interactions in the labor market of the Republic of Uzbekistan using a modified gravity model based on the integration of principal component analysis (PCA) and a simplified version of the DEMATEL algorithm. The study proposes an approach to forming a region’s “labor mass” as an aggregated indicator describing the condition and structure of the regional labor market based on five key indicators. A matrix of gravitational interactions between regions is constructed, reflecting the intensity of potential labor flows while accounting for spatial factors. Centers of economic attraction and peripheral regions are identified. The research results reveal pronounced spatial heterogeneity in Uzbe kistan’s labor market and confirm the existence of stable labor centers (Tashkent city, Tashkent region, and the Fergana Valley) as well as regions with limited connectivity. The proposed approach can be applied to monitor regional labor market imbalances, support the development of regional employment programs, and assess the impact of spatial factors on labor market dynamics.
Keywords: labor market; interregional economic interactions; gravity model; regional labor potential; principal component analysis (PCA); spatial differentiation; labor mobility